Coercive commodities and the political economy of involuntary consumption: The case of the gambling industries. (December 2017) - Young, Martin; Markham, Francis
Coercive commodities are those goods and services that promote 'akratic' consumption – that consumption recognised by consumers themselves to be contrary to their own best interests, all things considered. The production of coercive commodities has become an increasingly significant economic project of fractions of the capitalist class. As a form of secondary exploitation, coercive commodities facilitate the extraction of surplus profits from the savings and assets of the working classes, thus impeding the accumulation of a workers' hoard that may act as a potential blockage to value realisation in consumption. We use the example of commercial gambling to illustrate the political economy of coercive commodity production. The gambling production system is driven by a core dynamic between spatially fixed capital, the pressures of competition, and the technological generation of akrasia. The geographical expression of this dynamic is determined by the contingencies of the 'harm maximisation' policies of the state and the political efforts of individual capitalists to gain and reproduce monopoly power. Gambling production is effective as a form of secondary exploitation because, in addition to the profits accrued by exploiting labour, it extracts surplus profits by diverging sale price from value, by harnessing monopoly power, and by increasing the volume of consumption through akrasia. It is this extractive power, amplified by the consumer credit system, that forms the basis of the systemic utility of coercive commodities in late capitalist economies.